A Benchtop Method for Appending Protic Functional Groups to N‐Heterocyclic Carbene Protected Gold Nanoparticles. (12th March 2020) - DeJesus, Joseph F.; Sherman, Lindy M.; Yohannan, Darius J.; Becca, Jeffrey C.; Strausser, Shelby L.; Karger, Leonhard F. P.; Jensen, Lasse; Jenkins, David M.; Camden, Jon P.
Abstract: The remarkable resilience of N‐heterocyclic carbene (NHC) gold bonds has quickly made NHCs the ligand of choice when functionalizing gold surfaces. Despite rapid progress using deposition from free or CO2 ‐protected NHCs, synthetic challenges hinder the functionalization of NHC surfaces with protic functional groups, such as alcohols and amines, particularly on larger nanoparticles. Here, we synthesize NHC‐functionalized gold surfaces from gold(I) NHC complexes and aqueous nanoparticles without the need for additional reagents, enabling otherwise difficult functional groups to be appended to the carbene. The resilience of the NHC−Au bond allows for multi‐step post‐synthetic modification. Beginning with the nitro‐NHC, we form an amine‐NHC terminated surface, which further undergoes amide coupling with carboxylic acids. The simplicity of this approach, its compatibility with aqueous nanoparticle solutions, and its ability to yield protic functionality, greatly expands the potential of NHC‐functionalized noble metal surfaces. Abstract : Eine direkte und robuste Methode für die Funktionalisierung von SERS‐aktiven Gold‐Nanopartikeln mit bifunktionellen N‐heterocyclischen Carbenen wird vorgestellt. Die Methode bietet Zugang zu Amin‐funktionalisierten Oberflächen und ermöglicht es, die Amid‐Kupplung durch SERS zu verfolgen.